PENERAPAN SYARIAT ISLAM DALAM LINTASAN SEJARAH DAN HUKUM POSITIF DI INDONESIA - John Kenedi (Universitas Islam Negeri Fatmawati Sukarno, 2017)
Indonesia is a country that provides the widest opportunity for its citizens to embrace and run the religious syariat.Sebagai country with the largest Muslim population in the world, it is proper that the Muslim population dream of the realization of the application of Islamic Shari’ah in all joints of life. Application of Islamic Shari’a partially in every region of archipelago ever occurred during the reign of the empire. Reflecting on past successes, the same effort con- tinues in various phases of the history of the Indonesian nation from the era of independence to the Reformation era. Recorded various theories ever made by the legal experts with regard to the existence of Islamic Sharia in the country. Starting from the theory of ReceptieinComplexu by van den Berg, followed by Receptie and Receptie Exit theory, each of which was initiated by Snouck Hurgronje and Hazairin, to the theory of Receptiea Contrario which was born from the thought of Sajuti Thalib, including and Existence theory which became the concept of Islamic law enforcement in in the legal system of Indonesia. The latter theory is constantly being used in legitimizing the application of Islamic Sharia in Indonesia. Through the structural and cultural approach coupled with the use of its supporting factors, there is still hope for Muslims to realize his ideals. Issuance of Regional Regulations with nuances of Islam is a tendency that is done by every region that envisions the enforcement of Islamic Shari’a. However, such structural approaches still have prob- lems which require a law that can be specifically used as the basis for ensuring that Islamic Shari’a law can be applied